1999
DOI: 10.1017/s0022377898007223
|View full text |Cite
|
Sign up to set email alerts
|

Growth and saturation of the Kelvin–Helmholtz instability with parallel and antiparallel magnetic fields

Abstract: We investigate the Kelvin-Helmholtz instability occuring at the interface of a shear flow configuration in 2D compressible magnetohydrodynamics (MHD). The linear growth and the subsequent non-linear saturation of the instability are studied numerically. We consider an initial magnetic field aligned with the shear flow, and analyze the differences between cases where the initial field is unidirectional everywhere (uniform case), and where the field changes sign at the interface (reversed case). We recover and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
126
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 18 publications
15
126
0
Order By: Relevance
“…For strong initial fields, corresponding to an initial Alfvén number A = 5, we observe in accordance with Keppens et al (1999) a destabilization of the shear layer with respect to the non-magnetic case.…”
Section: Anti-parallel Initial Fieldssupporting
confidence: 85%
See 2 more Smart Citations
“…For strong initial fields, corresponding to an initial Alfvén number A = 5, we observe in accordance with Keppens et al (1999) a destabilization of the shear layer with respect to the non-magnetic case.…”
Section: Anti-parallel Initial Fieldssupporting
confidence: 85%
“…A magnetic field is known to reduce the growth rate and potentially, i.e., for A < 2, even to suppress the instability (Chandrasekhar 1961;Miura & Pritchett 1982;Keppens et al 1999). However, less is known about the saturation level and the dynamic back-reaction, in particular for weak initial fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the direction of the magnetic field with respect to the shear flow, a magnetic field might (de)stabilize KH instabilities (Miura & Pritchett 1982;Keppens et al 1999). Miura & Pritchett (1982) found that in a sheared magnetohydrodynamical flow in a compressible plasma, modes with kΔ < 2 are unstable, with Δ the scale length of the shear layer and k the wavenumber.…”
Section: Discussionmentioning
confidence: 99%
“…For the transverse case (B 0 ⊥ u 0 ), only the fast magnetosonic mode is destabilized, but if k · B 0 0, the instability contains Alfvén-mode and slow-mode components as well. Keppens et al (1999) studied the case of an initial magnetic field aligned with the shear flow. In the case the initial magnetic field is unidirectional everywhere (uniform case), the growth of KH instabilities is compressed, while a reversed field (i.e.…”
Section: Discussionmentioning
confidence: 99%